Neurological assessment head trauma - Williams & Wilkins (Baltimore : Williams & Wilkins, 1996)
(Producer) This highly interactive multimedia program presents a guided tutorial demonstrating appropriate neurological assessment and documentation of the neurological exam, along with'expert' clinical advice throughout the entire program. Following the tutorial, four case studies are randomly generated, giving the learner an opportunity to apply critical thinking skills, prioritize care, and make clinical decisions in a non-threatening environment
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: IBM-PC compatible computer with a 486 66 MHz or faster CPU; 8 MB of RAM; Windows 3.1 or higher; double speed CD-ROM player; SVGA display with a minimum of 256 col. mode; video accelerator preferred; Windows compatible sd. card
Keywords: Neurologic Examination -- methods; Craniocerebral Trauma -- diagnosis